Pelaksanaan Tradisi Perkawinan Merariq (Besebo) Suku Sasak di Lombok Timur - Ratu Muti’ah Ilmalia; I Nyoman Putu Budiartha; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2021)
The Merariq (Besebo) Marriage Tradition is a traditional marriage tradition in the Sasak Tribe, starting from the Memaling incident, also called stealing on the basis of the consent of a woman whose rights are still in the power of her parents, to prove as a form of chivalry as well as a form of the man's seriousness to marry the girl. Every Merariq profession has values ​​or morals of life that can become a guide for life for the community. The purposes of this study are to reveal the implementation of the merariq (besebo) marriage tradition in the Sasak tribe in East Lombok and the application of the merariq (besebo) marriage tradition according to Law No. 1 of 1974 and the Compilation of Islamic Law (KHI). The type of research used is Empirical Law research with a statutory approach and case approach. Data collection techniques in normative legal research are carried out by literature studies on legal materials. Sources of legal materials used are primary and secondary data. The data analysis technique is done by analytical descriptive. The results of the study revealed that the merariq tradition in the Sasak Tribe area has a picture of the marriage tradition with various rituals, where the traditional rituals are able to provide social value, and a moral message that is very attached to the Sasak people in East Lombok.